(untitled) (Quinto Sol, 2021)
This paper identifies and characterizes a corporate network based on Argentinian-Spanish business (Catalan mainly) that was built around a dozen companies all located in Buenos Aires, in the first half of 20th century. Studying the board of directors of the company Providencia Compañía Argentina de Seguros, it finds meeting points in which different groups are involved and it analyzes what corporate strategies they applied. It also determines whether any political compromise was acquired by the members of the network, both in Spain and Argentina.